2018
DOI: 10.1103/revmodphys.90.021001
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium : Excitons in atomically thin transition metal dichalcogenides

Abstract: Atomically thin materials such as graphene and monolayer transition metal dichalcogenides (TMDs) exhibit remarkable physical properties resulting from their reduced dimensionality and crystal symmetry. The family of semiconducting transition metal dichalcogenides is an especially promising platform for fundamental studies of two-dimensional (2D) systems, with potential applications in optoelectronics and valleytronics due to their direct band gap in the monolayer limit and highly efficient light-matter couplin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

47
1,626
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,703 publications
(1,684 citation statements)
references
References 280 publications
(399 reference statements)
47
1,626
0
11
Order By: Relevance
“…In recent years, excitons—i.e., electron–hole pairs bounded through their mutual Coulomb interaction—in 2D materials like TMDCs have attracted a great deal of attention due to their singular optical properties . These, to a great extent, reflect the presence of 2D excitons with large binding energies (hundreds of meV), thereby making such collective excitations stable even at room temperature.…”
Section: Strong Light–matter Interactions In Layered Transition Metalmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, excitons—i.e., electron–hole pairs bounded through their mutual Coulomb interaction—in 2D materials like TMDCs have attracted a great deal of attention due to their singular optical properties . These, to a great extent, reflect the presence of 2D excitons with large binding energies (hundreds of meV), thereby making such collective excitations stable even at room temperature.…”
Section: Strong Light–matter Interactions In Layered Transition Metalmentioning
confidence: 99%
“…This is in stark contrast with excitons in conventional bulk 3D semiconductors which typically possess binding energies of the order of kBT (where kBT26 meV at T = 300 K). The reason for this order‐of‐magnitude difference lies in inherently reduced screening in two dimensions …”
Section: Strong Light–matter Interactions In Layered Transition Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…The valley Hall effect in monolayer TMDCs is closely related to valley circular dichroism,84,85 where the carriers give rise to opposite Hall currents in opposite valleys 86–88. Under the illumination of circularly polarized light and an in‐plane electric field, populations of carriers with opposite signs will accumulate in +K and −K valleys of monolayer TMDCs, respectively, as shown in Figure 2a.…”
Section: Valley Excitons and Pseudospins In 2d Tmdcsmentioning
confidence: 99%
“…In early studies, it was observed that PL polarization retention is independent of the substrate 9. It approaches unity at low temperature9,85 but is significantly lower (≈40% for monolayer MoS 2 and ≈10% for WS 2 ) at RT 85–87. Later in 2016, Nayak et al reported a world record of valley polarization contrast of 35% for monolayer WS 2 , achieved by using near‐resonant below‐bandgap excitation and chemical vapor deposition (CVD) grown monolayer WS 2 92.…”
Section: Valley Excitons and Pseudospins In 2d Tmdcsmentioning
confidence: 99%